Effect of a carotene concentrate on the growth of human breast cancer cells and pS2 gene expression - Nesaretnam, Kalanithi; Jin Lim, Eu; Reimann, Karin; Lai, Leslie C. (undefined, 2000)
Breast cancer is the most common cancer in women worldwide. The growth of breast cancer cells is either hormone-dependent or hormone-independent. Both types are represented in vitro by the estrogen-receptor positive (ER+) MCF-7 and the estrogen-receptor negative (ER-) MDA-MB-231 cell lines, respectively. The pS2 gene is an estrogen-regulated gene and serves as a marker for the ER+ tumours. Carotenoids are pigments with anti-cancer properties besides having pro-vitamin A, antioxidant and free-radical quenching effects. This study was designed firstly, to compare the effect of palm oil carotene concentrate with retinoic acid on the growth of the ER+ MCF-7 and the ER- MDA-MB-231 cells; and secondly to evaluate the effect of the palm oil carotene concentrate on the regulation of pS2 mRNA. The growth experiments were performed with monolayer cells seeded in phenol red free RPMI 1640 culture media and subsequently treated with varying concentrations of either retinoic acid or palm oil carotenoids. The cell numbers were determined at the start of each experiment and then at successive time intervals. The results showed that the palm oil carotene concentrate caused dose-dependent inhibition of estradiol-stimulated growth of MCF-7 cells but did not affect the proliferation of MDA-MB-231 cells. Retinoic acid caused similar, albeit more potent effects, as significant inhibition was observed at lower concentrations than the palm oil carotenoids. In the pS2 gene expression experiment, cell monolayers were treated with the carotene concentrate (10-6 M), either with or without supplemented estradiol (10-8 M), and subsequently the RNA was extracted. Northern blotting was performed and the regulation of pS2 mRNA determined using a 32P-labelled pS2 cDNA probe. The results showed that the palm oil carotene concentrate did not affect the expression of pS2 mRNA and are therefore independent of the estrogen-regulated pathway. Copyright (C) 2000 Elsevier Science Ireland Ltd.